Auditoría de gestión y su relación con la eficiencia del área de talento humano de la corporación latinoamericana de Software S.A. cantón Guayaquil, año 2013 - Anzules Pacheco, María Victoria (2015)
This research was conducted in the city of Guayaquil in the Latin American Enterprise Software Corporation SA CORLASOSA, in order to conduct an audit of management in the area of Human Resource of the company and determine the level of efficiency and effectiveness with which the assigned activities are met. The development of research is divided into chapters, divided into five phases, for which a fictitious accounting firm, which is called designing VA Partners. The types of research used were bibliographical and field, which have contributed to the construction of relevant information related to the audit process of human talent and the methods used were analytical, deductive and inductive, selecting as audit method method internal control COSO I, for a total of 15 questions properly structured whose result determines a risk level of 23% was designed, the inherent risk has been calculated based on a weighting matrix of four factors that can affect the normal development of the company, which determine 55% risk and the risk of detection was set at 12%, to obtain audit risk 5.08% eventually among the findings are: Inadequate implementation of the plan motivation and incentives, lack of performance indicators to measure the performance of staff, high staff turnover, closed communication channels